Biochemical blood parameters and level of endogenous intoxication in cows suffering from hepatopathies under heat stress - E. V. Kuzminova; E. N. Rud; M. P. Semenenko; A. A. Abramov (Ветеринария сегодня)
Global warming results in increased extreme weather  events, including heatwaves,  droughts and floods, which exceed plants’and animals’tolerance thresholds, thus posing a threat to the economy and agriculture. Under these conditions, heat stress becomes a vital problem for animal husbandry. The paper presents the study results of biochemical blood parameters and endogenous intoxication in cows suffering from hepatopathies  under heat stress. Based on the calculated temperature-humidity  index, it was established that during the summer season in the conditions of the Krasnodar  Krai lowlands, cows are under heat stress. Using the method of paired comparisons, two groups of animals (n = 10) were formed: the first group was a healthy livestock; and the second group consisted of animals suffering from hepatic pathologies.  Blood was sampled from all cows at the beginning of the experiment (the first decade of May) and at the end (the last decade of July). Laboratory tests of blood revealed that as the heat stress develops healthy cows show the increase in the protein concentration in blood, and, on the contrary, animals with hepatic pathologies demonstrate the inhibition of protein synthesis. The higher activity of aminotransferases and alkaline phosphatase in the bovine serum in the summer season when compared to the spring season was established. The study of the endogenous intoxication level dynamics in cattle during the development of heat stress, showed that in both groups the concentrations of middle molecules (ММ) increased relative to the background data: in the first group (healthy cows) MM 237 – by 11.8%,  MM 254 – by 14.4%,  MM 280 – by 16.9%; in the second group (cattle with liver pathology)  MM 237 – by 16.9%,  MM 254 – by 20.3%,  MM 280 – by 33%. Thus, under heat stress, the endogenous intoxication in healthy livestock was almost 1.5 times less intense as compared to the animals suffering from hepatopathies.